Evidence of parallel evolution in the dental elements of Sweetognathus conodonts - Petryshen, W.; Henderson, C. M.; de Baets, Kenneth; Jarochowska, Emilia (Proceedings of the Royal Society of London, Series B: Biological Sciences, 2020)
The repeated emergence of similar morphologies in the dental elements of Permian Sweetognathus conodonts has been a hypothesized example of parallel evolution. To test if morphological parallelisms occur between isolated Sweetognathus lineages, this study uses two-dimensional-based geometric morphometrics combined with a revised and expanded phylogeny of Permian Sweetognathus conodonts to quantify dental element trait distributions and compare the phenotypic trajectories between lineages. A hierarchical clustering method was used to identify recurrent species pairs based on principal component scores describing their morphological variation, with the further incorporation of widely used ecological metrics such as limiting similarity and morphological overlap. Our research implies that a major contributor to conodont diversity in Palaeozoic marine trophic networks is the emergence of recurrent parallel morphologies via disruptive and directional selection. This study illustrates the mechanisms through which conodonts achieved their status as hyper-diverse predators and scavengers, contributing substantially to the complexity of Palaeozoic marine communities.
CRIS-Team Scopus Importer:2020-11-27
Keywords: conodont trophic networks; parallel evolution; Sweetognathus